Nilai Pendidikan Islam dalam Tradisi Potong Rambut Bayi pada Masyarakat Muslim Ketapang, Kalimantan Barat - Aziz, Abdul; Sy, Syamhadi; Kurnia, Kurnia (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2024)
The tradition of shaving babies' hair in the Ketapang community is still preserved today, even though there are pros and cons to it. For this reason, this research aims to determine the history, implementation, and values ​​of Islamic education in the tradition of shaving babies' hair in the Kalinilam Muslim community, Ketapang Regency, West Kalimantan. This type of research uses qualitative. Data collection techniques use interviews, observation and documentation. The data sources come from informants, namely religious leaders, community leaders, and the people of Ketapang Regency. The data analysis used is ethnographic, namely knowing the history and value of Islamic education and the tradition of shaving babies' hair carried out by the Muslim community in Kalinilam village, Ketapang Regency, West Kalimantan. The results of this research are: 1) The tradition of shaving babies' hair in the Muslim community in Kalinilam Village, Ketapang Regency, has been carried out from generation to generation, inherited by the ancestors of the local community. 2) The implementation is done in two stages: pre-implementation and preparing the tools and materials you want. Second, the implementation process (core), namely several sacred steps that must not be abandoned. 3). The educational values found in the tradition of shaving babies' hair are values ​​of faith, morals, love of the country, and responsibility. This research can benefit the broader community so that similar traditions continue to be preserved, especially by the Muslim community of Kalinilam, Ketapang Regency, and introduced to the younger generation so that they know and continue to practice.